PENGARUH GAYA KEPEMIMPINAN DAN REWARD TERHADAP GAIRAH KERJA KARYAWAN PADA PT.TOBA PERMAI MEDAN - Fanny Untary; Syawaluddin Syawaluddin; Mila Asmawiani (JURNAL BISNIS KOLEGA, 2020)
Abstract. PT.Toba Permai Medan is: a company engaged in the paper trade. The phenomenon that occurs in company is: decreased employee morale. Employees do not have an interest in improving their work, they only complete the responsibilities given but there is no intention to improve work efficiency and effectiveness. The cause of decreased employee morale is thought to be caused by leadership style and rewards. This study uses multiple linear regression analysis. The population in this study was all employees in the company, amounting to 45 people. Samples were taken with a saturated sampling technique where all members of the population were used as samples. Thus, the sample in this study amounted to 45 people. Simultaneous hypothesis test results show that the leadership style and reward variables have an influence on employee morale at PT.Toba Permai Medan. The results of the partial hypothesis test showed that partially each of the leadership style and reward variables had an influence on employee morale at PT.Toba Permai Medan.Â Â Keywords: Leadership Style, Reward, Employee Morale.